THE ECONOMIC FACTORS AND OTHER VARIABLES THAT AFFECT THE EMPOWERMENT OF THE MICRO-BUSINESSES RUN BY FARMING COMMUNITIES IN VILLAGES AROUND THE FOREST AREAS - Yoyo Sunaryo Nitiwijaya; Hajanirina Andrianantenaina (Journal of Indonesian Economy and Business (JIEB), 2016)
This research is conducted in Kuningan regency, West Java, Indonesia and aims to analyze the economic, social, institutional, and cosmopolitan factors which affect the empowerment of the communities of micro-business entrepreneurs. It attempts to investigate the problems that persist for this community, in that the people living near the forest are heavily dependent on it, and on their agricultural activities. They have to face institutional regulations and competition from immigrants. Due to the nature of the data, the complexity of the structured relationship, the multiple endogenous variables; SEM or Structural Equation Modeling is used to analyze and confirm the extant association between the studied variables in a covariance based approach assisted by AMOS. The results suggest that the micro-business community is strongly influenced by the dynamics of the institutional businesses in the village, their social interactions, economic capabilities and cosmopolitan drives with the immigrant communities. It shows the efficiency and importance of the institutional community while dealing with micro-businesses’ agrarian economic empowerment. Improvement in the regulations is necessary and is expected to improve the partnership between the government and private and public entities, to cope with the economic development of society in such communities, and others which may share the same characteristics.